Preparation method of ZIF-67 derived cobalt-manganese catalyst and application of ZIF-67 derived cobalt-manganese catalyst in catalytic oxidation of benzene
ZIF-67-derived cobalt-manganese catalysts were prepared by etching with potassium permanganate. By optimizing the pore structure and active components, the problems of high space velocity, low temperature and stability of ZIF-67 catalysts in the catalytic oxidation of benzene were solved, and efficient and economical catalytic oxidation was achieved.
Patent Information
- Application Number
- CN202511537407.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-27
- Publication Date
- 2025-11-25
- Estimated Expiration
- 2045-10-27
AI Technical Summary
Existing ZIF-67 catalysts struggle to balance high space velocity, low reaction temperature, and long-term stability when catalyzing the oxidation of benzene. Furthermore, residues are easily left behind during the preparation process, leading to a decrease in catalytic activity.
Potassium permanganate was used as an etchant and reacted with ZIF-67 suspension through a hydrothermal reaction to form a ZIF-67-derived cobalt-manganese catalyst. This optimized the pore structure and surface active components, forming Co-Mn synergistic active centers and avoiding residual impurities.
This method achieves efficient catalytic oxidation of benzene under high space velocity and low temperature conditions. The catalyst has high purity and good long-term stability, which significantly improves catalytic activity and lifespan, and reduces energy consumption and production costs.
Smart Images

Figure CN121004004A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a method for preparing a ZIF-67 derived cobalt-manganese catalyst and its application in the catalytic oxidation of benzene. Background Technology
[0002] Volatile organic compounds (VOCs) are among the major pollutants causing acid rain, photochemical smog, and global climate change, posing serious threats to the ecological environment and human health. Benzene (C6H6), a typical aromatic VOC, is highly toxic, carcinogenic, and mutagenic due to its unique structure, and is difficult to treat, making it a hot topic and challenge in air pollution control. Methods for benzene removal mainly include adsorption, absorption, thermal combustion, biodegradation, low-temperature plasma, photocatalysis, and catalytic oxidation. Among these, catalytic oxidation is considered one of the most effective VOC removal methods due to its high efficiency, fewer byproducts, and low cost. The core bottleneck of this technology lies in developing non-precious metal catalysts that possess high activity, excellent stability, and low cost. Among non-precious metal catalysts, metal-organic framework (MOF)-derived catalysts, with their ability to flexibly control active components and unique pore structure, provide ideal precursors for constructing efficient multi-metal synergistic catalytic systems.
[0003] In MOF systems, ZIF-67-derived catalysts have shown considerable potential. Cobalt-based catalysts derived from ZIF-67 precursors possess advantages such as controllable structure, tunable active components, and favorable pore structure. Lei Juan et al.'s study on the catalytic oxidation performance of VOCs using ZIF-67@Co3O4, using ZIF-67 as a precursor and prepared catalysts at different calcination temperatures, while exhibiting MOF-derived structural characteristics, still faced challenges in achieving a space velocity of 20000 mL / (g·h) in the catalytic oxidation of benzene and a 90% benzene conversion rate at reaction temperatures ranging from 254℃ to 295℃. These catalysts still exhibited poor low-temperature benzene oxidation activity and low space velocity. To improve the low-temperature oxidation activity of benzene, ZIF-67 is usually used as the base, and different methods are used to introduce active components to prepare catalysts with different morphologies. Existing methods include complexing agent-assisted method, co-precipitation method, template method, sol-gel method, etc. However, all of the above methods have residues that are difficult to completely remove. Moreover, when the catalysts prepared by the existing methods are to achieve a benzene conversion rate of 90%, it is difficult to simultaneously achieve high space velocity, low reaction temperature and long-term stability.
[0004] To overcome the aforementioned bottlenecks, it is urgent to improve catalytic performance by introducing new active components and regulating the microstructure. Summary of the Invention
[0005] Purpose of the invention: This invention proposes a method for preparing a ZIF-67-derived cobalt-manganese catalyst and its application in the catalytic oxidation of benzene. The purpose is to solve the problems that existing methods for preparing ZIF-67 catalysts often leave residues, and that when ZIF-67 catalysts achieve a 90% benzene conversion rate, it is difficult to simultaneously achieve high space velocity, low reaction temperature, and long-term stability.
[0006] Technical means: The first aspect of this invention provides a method for preparing a ZIF-67 derived cobalt-manganese catalyst, comprising the following steps: S1. Preparation of ZIF-67 precursor; S2. Disperse ZIF-67 in water to form a suspension. Add an equal volume of ZIF-67 suspension to potassium permanganate aqueous solution to carry out an etching reaction. The mass concentration ratio of ZIF-67 suspension to potassium permanganate aqueous solution is 5:1 to 2 to obtain a mixed system. S3. The mixture is transferred to a reactor for hydrothermal reaction to obtain a black precipitate; S4. The black precipitate is washed, dried, calcined, and ground to obtain the ZIF-67 derived cobalt-manganese catalyst.
[0007] Preferably, in step S1, the method for preparing the ZIF-67 precursor is as follows: under magnetic stirring, an aqueous solution of cobalt nitrate hexahydrate is rapidly poured into an aqueous solution of 2-methylimidazole, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 2-6:1, and the mixture is stirred continuously at room temperature for 2-6 hours. After centrifugation to separate the solid product, it is washed 3-5 times with deionized water and dried in an oven at 60-90°C for 10-14 hours to obtain a purple solid. After grinding, ZIF-67 powder is obtained.
[0008] Preferably, in step S2, the mass concentration ratio of ZIF-67 suspension to potassium permanganate aqueous solution is 5:2.
[0009] Preferably, in step S3, the hydrothermal temperature is 100℃~160℃, and the reaction time is 4h~8h.
[0010] Preferably, the hydrothermal temperature is 120℃~140℃.
[0011] Preferably, in step S4, the calcination temperature is 350℃~500℃ and the calcination time is 2h~4h.
[0012] Preferably, the ZIF-67 derived cobalt-manganese catalyst has a pore volume of up to 0.59 cm³. 3 / g, with a pore size of up to 16.2 nm.
[0013] The second aspect of this invention provides the application of the ZIF-67 derived cobalt-manganese catalyst prepared by the method described above in the catalytic oxidation of organic compounds.
[0014] The present invention also proposes the application of the ZIF-67 derived cobalt-manganese catalyst prepared by the method described above in the catalytic oxidation of benzene. Beneficial effects
[0015] This invention improves the high-space-velocity, low-temperature catalytic oxidation activity of ZIF-67 derived catalysts by controlling hydrothermal parameters and the mass ratio of cobalt and manganese sources, adjusting the catalyst pore structure, and optimizing the surface active components. Under optimized hydrothermal conditions, potassium permanganate oxidation etching promotes the oxidation of Co in the ZIF-67 framework. 2+ A redox reaction occurs with permanganate ions to construct a cobalt-manganese synergistic active center in one step. By optimizing the amount of potassium permanganate etching, the pore structure of the material can be precisely controlled to form a better mesoporous structure. The larger pore volume and pore size significantly reduce mass transfer resistance, making it easier for reactant molecules to contact the active sites, thereby improving reaction efficiency.
[0016] This invention uses potassium permanganate as an etchant, which offers significant advantages over traditional methods such as complexing agent-assisted etching, co-precipitation, template etching, and sol-gel etching, particularly in terms of "cleanliness." Potassium permanganate etches ZIF-67 through an oxidation reaction, and its conversion products are entirely inorganic (such as manganese ions), leaving no harmful impurities in the catalyst system. In contrast, traditional methods often suffer from residual contaminants—for example, complexing agent-assisted etching may leave behind incompletely removed complexing agents, and template etching may leave behind template agents. These residues can occupy active sites on the catalyst, interfere with its electronic structure, or trigger side reactions, leading to decreased catalytic activity or even deactivation. The potassium permanganate etching process used in this invention is thorough, and the conversion products have good compatibility with the catalytic system, without negatively impacting subsequent reactions. This not only maximizes the purity of the catalyst but also significantly improves its long-term stability and lifespan. Therefore, the "no harmful residue" characteristic of potassium permanganate as an etchant is its core advantage over traditional methods, successfully solving the problem of catalyst performance degradation caused by residual impurities.
[0017] This invention exhibits excellent low-temperature catalytic activity. The Co-Mn8-T prepared by the method of this invention... 140The catalyst exhibits excellent low-temperature activity in the catalytic oxidation of benzene. Under reaction conditions with a space velocity as high as 60,000 mL / (g·h), a benzene concentration of 1000 ppm, and an oxygen content of 20%, the catalyst can achieve a benzene conversion rate of 90% at a reaction temperature of approximately 210 °C. This excellent low-temperature activity indicates that the catalyst can efficiently catalyze the oxidation of benzene under relatively low energy consumption conditions, demonstrating significant application potential and economic benefits.
[0018] The preparation process of this invention is simple and easy to implement, with mild and controllable conditions. Using ZIF-67 as a precursor, its synthesis can be achieved simply by mixing and stirring at room temperature, without the need for complex equipment or harsh conditions. Subsequent etching steps are straightforward, and the calcination process is within conventional limits. The entire process flow is clear, the raw materials are readily available, and it involves only routine stirring, centrifugation, hydrothermal treatment, and calcination operations, significantly reducing the difficulty of preparation, equipment requirements, and production costs. Attached Figure Description
[0019] Figure 1 The XRD patterns are of the catalysts prepared in Example 1 and Comparative Example 1 of this invention. Figure 2 EPR diagrams of the catalysts prepared in Example 1 and Comparative Example 1 of this invention; Figure 3 This is a SEM image of the catalyst prepared in Example 1 of the present invention; Figure 4 Here is a SEM image of the catalyst prepared in Comparative Example 1 of this invention; Figure 5 The N2 adsorption-desorption curves of the catalysts prepared in Example 1 and Comparative Example 1 of this invention are shown. Figure 6 This is a graph showing the long-term stability and cyclic testing of Embodiment 1 of the present invention. Detailed Implementation
[0020] The beneficial effects of the present invention are demonstrated by the following examples.
[0021] To better explain and facilitate understanding of the present invention, the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0022] This invention proposes a method for preparing a ZIF-67-derived cobalt-manganese catalyst and its application in the catalytic oxidation of benzene. This invention uses potassium permanganate, a strong oxidant, to etch ZIF-67. Compared to other oxidants (such as potassium dichromate and chlorate), potassium permanganate produces Mn as a reduction product of KMnO4. 2+ It has low toxicity, no harmful residues, and is more in line with the requirements of green chemistry.
[0023] The reaction equation is as follows: Co 2+ +MnO4− +8 H + →Co 3+ +Mn 2+ +4 H2O Potassium permanganate is a strong oxidizing agent (standard electrode potential: +1.51V, acidic conditions) and can selectively oxidize Co in ZIF-67. 2+ To higher price state Co 3+ After calcination, active species such as Co3O4 are formed, which enhances the activity of catalytic oxidation reactions. The surface morphology of ZIF-67 can be controlled by oxidation etching (such as forming a porous structure), increasing the specific surface area and the exposure of active sites.
[0024] This invention employs a high space velocity of 60,000 mL / (g·h), which is significantly higher than the low space velocity of less than 30,000 mL / (g·h) in conventional industrial catalysis. It addresses the problems of large reactor volumes, high equipment investment, and long material residence times that easily lead to side reactions caused by low space velocities in existing industrial catalysis processes. For example, in benzene oxidation, excessively long residence times result in increased byproducts such as CO and a significant decrease in degradation rate. However, the high mass transfer efficiency brought about by the high active site density and reasonable mesoporous structure of the catalyst enables benzene to complete the reaction within a short residence time in the catalyst bed, significantly improving industrial processing capacity while effectively suppressing side reactions.
[0025] This invention features a low reaction temperature of 210°C, far lower than the conventional industrial high temperature of over 300°C. It overcomes the problems of high energy consumption, short catalyst life, and high operational safety risks caused by high temperatures in existing technologies. Through the synergistic effect of Co-Mn bimetallic sites, it achieves high activity at low temperatures. Under the synergistic effect of high space velocity and low temperature, it breaks through the contradiction in existing industrial catalysis that "high space velocity requires high temperature to compensate for insufficient conversion rate, and low temperature requires low space velocity to ensure reaction time." It achieves the comprehensive advantages of high processing capacity, low energy consumption, and long life, effectively solving the pain point of existing technologies that are "either inefficient or costly," and meeting the industrial catalysis requirements for high efficiency, economy, and safety.
[0026] This invention proposes a method for preparing a ZIF-67 derived cobalt-manganese catalyst, comprising the following steps: (1) Preparation of ZIF-67 precursor: Under magnetic stirring, the aqueous solution of cobalt nitrate hexahydrate was quickly poured into the aqueous solution of 2-methylimidazole. The molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate was 2 to 6:1. The mixture was dried at room temperature for 10 to 14 hours with continuous stirring to obtain a purple solid. After grinding, ZIF-67 powder was obtained.
[0027] (2) Etching: A ZIF-67 suspension was prepared using deionized water. An equal volume of the ZIF-67 suspension was added to a potassium permanganate aqueous solution for etching. The mass concentration ratio of the ZIF-67 suspension to the potassium permanganate aqueous solution was 5:1–2, resulting in a mixed system. After stirring at room temperature for 1 hour, the mixture was transferred to a reactor lined with 100 mL of polytetrafluoroethylene and reacted at 100–140 °C for 4–8 hours under hydrothermal conditions. After cooling, the solid was separated by centrifugation, washed 3–5 times with deionized water, and dried at 60–90 °C for 10–14 hours to obtain the etched black powder.
[0028] (3) Calcination: The black powder is placed in a crucible and then placed in a muffle furnace. The temperature is increased to 350℃~500℃ at 2℃ / min and calcined for 2h~4h. After natural cooling, it is ground to obtain the catalyst Co-Mn. x -T y Take the mass ratio of potassium permanganate and ZIF-67 as x:20, where y is the hydrothermal temperature.
[0029] The catalyst Co-Mn prepared by the above method x -T y Through scanning electron microscope images, such as Figure 3 As shown, they all exhibit a loose, spherical morphology; the N2 adsorption-desorption curves, as shown... Figure 5 As shown, all exhibit typical Type IV isotherms (IUPAC classification) and H3 hysteresis loops, indicating that the materials possess typical mesoporous structure characteristics. Given the similarity in morphology and pore structure among catalysts prepared under different parameters, to clarify the influence mechanism of hydrothermal parameters and the mass ratio of cobalt and manganese sources on the pore structure regulation and surface active components of the catalysts, the following examples and comparative examples are compared using a single-factor substitution method.
[0030] Example 1: Catalyst Co-Mn8-T 140 Preparation and application (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0031] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.4g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1h, and then transfer it to a reaction vessel with a 100mL polytetrafluoroethylene liner. React at 140℃ under hydrothermal conditions for 6h. After cooling, centrifuge to separate the solid, wash it 3 times with deionized water, and dry it at 80℃ for 12h to obtain the etched black powder.
[0032] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn. x -T y The mass ratio of potassium permanganate to ZIF-67 was x:20, and y was the hydrothermal temperature. Therefore, the catalyst Co-Mn8-T was obtained. 140 .
[0033] Activity test: 0.1g of catalyst Co-Mn8-T was charged into a tube furnace reactor. 140 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 210℃.
[0034] Example 2: Catalyst Co-Mn8-T 100 Preparation and application (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0035] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.4g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1h, and then transfer it to a reaction vessel with a 100mL polytetrafluoroethylene liner. React at 100℃ under hydrothermal conditions for 6h. After cooling, centrifuge to separate the solid, wash it 3 times with deionized water, and dry it at 80℃ for 12h to obtain the etched black powder.
[0036] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn8-T. 100 .
[0037] Activity test: 0.1g of catalyst Co-Mn8-T was charged into a tube furnace reactor. 100 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 223℃.
[0038] Example 3: Catalyst Co-Mn8-T 120 Preparation (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0039] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.4g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1h, and then transfer it to a reaction vessel with a 100mL polytetrafluoroethylene liner. React at 120℃ under hydrothermal conditions for 6h. After cooling, centrifuge to separate the solid, wash it 3 times with deionized water, and dry it at 80℃ for 12h to obtain the etched black powder.
[0040] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn8-T. 120 .
[0041] 0.1 g of catalyst Co-Mn8-T was charged into the reactor of a tubular furnace. 120 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 217℃.
[0042] Example 4: Catalyst Co-Mn8-T 160 Preparation (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0043] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.4g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1h, and then transfer it to a reaction vessel with a 100mL polytetrafluoroethylene liner. React at 160℃ under hydrothermal conditions for 6h. After cooling, centrifuge to separate the solid, wash it 3 times with deionized water, and dry it at 80℃ for 12h to obtain the etched black powder.
[0044] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn8-T. 160 .
[0045] Activity test: 0.1g of catalyst Co-Mn8-T was charged into a tube furnace reactor. 160 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 225℃.
[0046] Example 5: Catalyst Co-Mn4-T 140 Preparation (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0047] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.2g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1h, and then transfer it to a reaction vessel with a 100mL polytetrafluoroethylene liner. React at 140℃ under hydrothermal conditions for 6h. After cooling, centrifuge to separate the solid, wash it 3 times with deionized water, and dry it at 80℃ for 12h to obtain the etched black powder.
[0048] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn4-T. 140 .
[0049] Activity test: 0.1g of catalyst Co-Mn4-T was charged into a tubular furnace reactor. 140 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 218℃.
[0050] Comparative Example 1: Preparation and Application of Catalyst Co3O4 (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0051] (2) Calcination: ZIF-67 powder was placed in a 50mL crucible and then placed in a muffle furnace. The temperature was increased to 450℃ at 2℃ / min and calcined for 2h. After natural cooling, it was ground to obtain the catalyst Co3O4.
[0052] Activity test: 0.1 g of catalyst Co3O4 was charged into a tubular furnace reactor, and a mixed gas of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) spectrometer. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 258℃.
[0053] Comparative Example 2: Preparation and Application of the Catalyst Co-Mn8-RT (1) Preparation of ZIF-67 precursor: 1 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0054] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.4g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 6h, centrifuge to separate the solid, wash with deionized water 3 times, and dry at 80℃ for 12h to obtain the etched black powder.
[0055] (3) After loading the black powder into a 50mL crucible, place it in a muffle furnace and calcine it at 450℃ for 2h at a rate of 2℃ / min. After natural cooling, grind it and stir at room temperature to obtain the catalyst Co-Mn8-RT.
[0056] Activity test: 0.1g of catalyst Co-Mn8-T was charged into a tube furnace reactor. 140 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 227℃.
[0057] Comparative Example 3: Catalyst Co-Mn8-T 180 Preparation (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0058] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.4g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1h, and then transfer it to a reaction vessel with a 100mL polytetrafluoroethylene liner. React at 180℃ under hydrothermal conditions for 6h. After cooling, centrifuge to separate the solid, wash it 3 times with deionized water, and dry it at 80℃ for 12h to obtain the etched black powder.
[0059] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn8-T. 180 .
[0060] Activity test: 0.1g of catalyst Co-Mn8-T was charged into a tube furnace reactor. 180 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 237℃.
[0061] Comparative Example 4: Catalyst Co-Mn1-T 140 Preparation (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0062] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.05g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1h, and then transfer it to a reaction vessel with a 100mL polytetrafluoroethylene liner. React at 140℃ under hydrothermal conditions for 6h. After cooling, centrifuge to separate the solid, wash it 3 times with deionized water, and dry it at 80℃ for 12h to obtain the etched black powder.
[0063] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn1-T. 140 .
[0064] Activity test: 0.1 g of catalyst Co-Mn1-T was charged into a tube furnace reactor. 140 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 230℃.
[0065] Comparative Example 5: Catalyst Co-Mn2-T 140 Preparation (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0066] (2) Etching: Disperse 1.0g of the above ZIF-67 powder in 30mL of deionized water, and denote it as suspension C; dissolve 0.1g of potassium permanganate in 30mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1h, and then transfer it to a reaction vessel with a 100mL polytetrafluoroethylene liner. React at 140℃ under hydrothermal conditions for 6h. After cooling, centrifuge to separate the solid, wash it 3 times with deionized water, and dry it at 80℃ for 12h to obtain the etched black powder.
[0067] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn2-T. 140 .
[0068] Activity test: 0.1 g of catalyst Co-Mn2-T was charged into a tubular furnace reactor. 140 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) instrument. Table 1 shows that the benzene conversion rate was 90% at a reaction temperature of approximately 228℃.
[0069] Comparative Example 6: Catalyst Co-Mn 16 -T 140 Preparation (1) Preparation of ZIF-67 precursor: 16 mmol of 2-methylimidazole was dissolved in 30 mL of deionized water and labeled as solution A; 4 mmol of cobalt nitrate hexahydrate was dissolved in 30 mL of deionized water and labeled as solution B. Solution B was quickly poured into solution A under magnetic stirring and stirred continuously at room temperature for 4 h. After centrifugation to separate the solid product, it was washed three times with deionized water and dried in an oven at 80 °C for 12 h to obtain a purple solid, which was then ground to obtain ZIF-67 powder.
[0070] (2) Etching: Disperse 1.0 g of the above ZIF-67 powder in 30 mL of deionized water, and denote it as suspension C; dissolve 0.8 g of potassium permanganate in 30 mL of deionized water, and denote it as solution D. Add solution D to suspension C, stir at room temperature for 1 h, and then transfer it to a reaction vessel with a 100 mL polytetrafluoroethylene liner. React at 140 °C under hydrothermal conditions for 6 h. After cooling, centrifuge to separate the solid, wash it three times with deionized water, and dry it at 80 °C for 12 h to obtain the etched black powder.
[0071] (3) Calcination: The black powder was placed in a 50 mL crucible and then placed in a muffle furnace. The temperature was increased to 450 °C at 2 °C / min and calcined for 2 h. After natural cooling, it was ground to obtain the catalyst Co-Mn. 16 -T 140 .
[0072] Activity test: 0.1 g of catalyst Co-Mn was charged into a tube furnace reactor. 16 -T 140 A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity of 60000 mL / (g·h). The results were detected using a Fourier transform infrared spectroscopy (FTIR) spectrometer. Table 1 shows that when the reaction temperature is 300℃, the catalyst Co-Mn... 16 -T 140 The conversion rate of benzene has not yet reached 90%.
[0073] Table 1. Summary of catalytic temperatures of each catalyst in the examples and comparative examples.
[0074] Based on the data in Table 1, a comparison between Example 1 and Comparative Example 1 reveals that without the potassium permanganate hydrothermal oxidation etching process, the catalyst obtained solely from ZIF-67 calcination exhibits poor catalytic performance. This indicates that the addition of the novel active metal component Mn can effectively enhance the catalyst's catalytic activity, demonstrating the synergistic effect of the Mn-Co bimetallic active centers, which is beneficial for the low-temperature catalytic oxidation of benzene.
[0075] Taking Example 1 as an example, Figure 1 The XRD test results of Example 1 and Comparative Example 1 are shown. Both Example 1 and Comparative Example 1 belong to spinel-type Co3O4. Although the catalyst Co-Mn8-T... 140 Despite undergoing hydrothermal etching with potassium permanganate and subsequent high-temperature calcination, the crystal structure of the ZIF-67 pyrolysis products remained unchanged. This indicates that the etching process preserved the ZIF-67-derived Co3O4 spinel framework, and its cubic crystal structure remained intact, providing a stable structural basis for the catalytic reaction. Furthermore, the catalyst Co-Mn8-T... 140The crystallinity decreased significantly, indicating that KMnO4 hydrothermal etching reduced the crystallinity of Co3O4, leading to the formation of more amorphous phases. This is conducive to the generation of more abundant oxygen vacancies, such as... Figure 2 As shown, the catalyst Co-Mn8-T 140 The presence of a more significant EPR symmetry signal confirms the presence of more oxygen vacancies, thereby enhancing catalytic activity. Meanwhile, the peak position red-shifts significantly with KMnO4 etching, which is due to the cell changes caused by the introduction of Mn into the Co3O4 crystal structure.
[0076] Figure 3 and Figure 4 The images shown are scanning electron microscope (SEM) images of Example 1 and Comparative Example 1, respectively. Figure 4 The dense spherical morphology of Co3O4 Figure 3 The catalyst Co-Mn8-T is clearly shown. 140 The more regular loose spherical morphology results in a more developed pore structure. The regular loose spherical structure helps to reduce gas diffusion resistance, and the open pores accelerate the transport of benzene molecules to the internal active sites and the desorption of products, effectively suppressing mass transfer limitations.
[0077] Figure 5 The N2 adsorption-desorption curves for Example 1 and Comparative Example 1 are shown. Both exhibit typical Type IV isotherms (IUPAC classification) and Type H3 hysteresis loops, indicating that the materials possess typical mesoporous structure characteristics. Catalyst Co-Mn8-T 140 The catalyst exhibits a more pronounced hysteresis phenomenon than Co3O4, which also indicates that Co-Mn8-T 140 The catalyst formed a richer porous structure during the etching process. Furthermore, Co-Mn8-T 140 The catalyst has a large pore volume and pore size, both of which are 0.59 cm. 3 / g and 16.2 nm. Larger pore volume and pore size can significantly improve the mass transfer efficiency of reactants, thereby increasing the reactivity.
[0078] Figure 6 The performance of Example 1 in cycling and stability experiments is demonstrated. 0.1 g of the catalyst Co-Mn8-T was charged into a tubular furnace reactor. 140A mixture of 1000 ppm benzene and 20% O2 was introduced, with N2 as the equilibrium gas, and a space velocity (HSV) of 60,000 mL / (g·h). The experiment was initially conducted at 240 °C, where the benzene conversion reached 100%. Subsequently, the temperature was lowered to 180 °C, and the benzene conversion decreased to approximately 13%. When the temperature was raised back to 240 °C, the benzene conversion recovered to 100%. This cycle was stably repeated five times over 25 hours. Notably, after the fifth cycle, the temperature was maintained at 240 °C for another 20 hours, and the benzene conversion remained at 100%, further demonstrating the long-term stability and lifespan of the catalyst.
[0079] Based on the data in Table 1, and by comparing Examples 1 to 4, and Comparative Examples 2 (RT) and 3 (180°C), it was found that the reaction temperature first decreased and then increased with increasing hydrothermal temperature. The optimal hydrothermal temperature was 120–140°C. When the space velocity was 60,000 mL / (g·h) and the reaction temperature was approximately below 220°C, the benzene conversion rate was 90%. Specifically, at a hydrothermal temperature of 140°C, a space velocity of 60,000 mL / (g·h), and a reaction temperature of 210°C, the benzene conversion rate was 90%. A separate comparison of Example 1 and Comparative Example 2 (RT) showed that the catalyst obtained under room temperature etching had a worse catalytic effect than that of Example 1 compared to the reaction under hydrothermal conditions at 140°C for 6 hours. This indicates that under hydrothermal conditions, potassium permanganate oxidation etching can more effectively promote the formation of Co in the ZIF-67 framework. 2+ The redox reaction with permanganate ions allows for a better construction of cobalt-manganese synergistic active centers, proving that hydrothermal etching is superior to room temperature etching.
[0080] Based on the data in Table 1, and by comparing Examples 1 and 5, as well as Comparative Examples 4 and 6, it was found that when the manganese-cobalt source mass ratio was 4–8:20, the benzene conversion rate was 90% at a space velocity of 60,000 mL / (g·h) and a reaction temperature approximately below 220°C. Specifically, when the manganese-cobalt source mass ratio was 8:20, the benzene conversion rate was 90% at a space velocity of 60,000 mL / (g·h) and a reaction temperature of 210°C.
[0081] In summary, under the conditions of a hydrothermal temperature of 140℃, a hydrothermal reaction time of 6h, and a potassium permanganate to ZIF-67 mass ratio of 8:20, the prepared Co-Mn8-T 140 The catalyst exhibits optimal activity for the catalytic oxidation of benzene. Under the conditions of a reaction temperature of 210℃, a space velocity of 60000 mL / (g·h), and a benzene concentration of 1000 ppm, the catalyst can achieve a benzene removal rate of up to 90%.
[0082] This invention utilizes a potassium permanganate hydrothermal etching method to prepare ZIF-67, precisely controlling the Co-Mn8-T... 140The catalyst has porous mass transfer channels, and a Co-Mn synergistic active center is constructed in one step, which effectively improves the low-temperature catalytic activity of the catalyst.
[0083] The above description is merely a preferred embodiment of the present invention, and the scope of protection of the present invention is not limited to the above embodiments. For those skilled in the art, any modifications, equivalent substitutions, or improvements made without departing from the technical concept of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a ZIF-67 derived cobalt-manganese catalyst, characterized in that, Includes the following steps: S1. Preparation of ZIF-67 precursor; S2. Disperse ZIF-67 in water to form a suspension. Add an equal volume of ZIF-67 suspension to potassium permanganate aqueous solution to carry out an etching reaction. The mass concentration ratio of ZIF-67 suspension to potassium permanganate aqueous solution is 5:1 to 2 to obtain a mixed system. S3. The mixture is transferred to a reactor for hydrothermal reaction to obtain a black precipitate; S4. The black precipitate is washed, dried, calcined, and ground to obtain the ZIF-67 derived cobalt-manganese catalyst.
2. The method for preparing a ZIF-67 derived cobalt-manganese catalyst according to claim 1, characterized in that, In step S1, the method for preparing the ZIF-67 precursor is as follows: Under magnetic stirring, an aqueous solution of cobalt nitrate hexahydrate is rapidly poured into an aqueous solution of 2-methylimidazole, with a molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate of 2-6:
1. The mixture is stirred continuously at room temperature for 2-6 hours. After centrifugation to separate the solid product, it is washed 3-5 times with deionized water and dried in an oven at 60-90°C for 10-14 hours to obtain a purple solid. After grinding, ZIF-67 powder is obtained.
3. The method for preparing a ZIF-67 derived cobalt-manganese catalyst according to claim 1, characterized in that, In step S2, the mass concentration ratio of ZIF-67 suspension to potassium permanganate aqueous solution is 5:
2.
4. The method for preparing a ZIF-67 derived cobalt-manganese catalyst according to claim 1, characterized in that, In step S3, the hydrothermal temperature is 100℃~160℃, and the reaction time is 4h~8h.
5. The method for preparing a ZIF-67 derived cobalt-manganese catalyst according to claim 1, characterized in that, The hydrothermal temperature is 120℃~140℃.
6. The method for preparing a ZIF-67 derived cobalt-manganese catalyst according to claim 1, characterized in that, In step S4, the calcination temperature is 350℃~500℃, and the calcination time is 2h~4h.
7. The method for preparing a ZIF-67 derived cobalt-manganese catalyst according to claim 1, characterized in that, The ZIF-67 derived cobalt-manganese catalyst achieved a pore volume of up to 0.59 cm³. 3 / g, with a pore size of up to 16.2nm.
8. The application of a ZIF-67 derived cobalt-manganese catalyst prepared by the method described in any one of claims 1-7 in the catalytic oxidation of volatile organic compounds.
9. The application of a ZIF-67 derived cobalt-manganese catalyst prepared by the method described in any one of claims 1-7 in the catalytic oxidation of benzene.
Citation Information
Patent Citations
Preparation method of core-shell-structured catalyst for low-temperature catalytic oxidation of toluene
CN110314685A
Cobalt oxide hollow polyhedral catalyst as well as preparation method and application thereof
CN114130394A
Preparation method of controllable etching MOFs (Metal-Organic Frameworks) derived low-temperature efficient doped VOCs (Volatile Organic Compounds) catalyst
CN115069264A
Surface-modified ZIFs-based monolithic catalyst and preparation method thereof
CN118320848A
VOC removal catalyst and method for producing the same as well as VOC removing method
JP2023057469A
Cited By
Hollow Mn-doped ZIF-67 composite electrode material and preparation method thereof
CN121892160A